2020
DOI: 10.1038/s41586-020-2638-5
|View full text |Cite
|
Sign up to set email alerts
|

Functionally uncoupled transcription–translation in Bacillus subtilis

Abstract: Coupled transcription and translation is considered a defining feature of bacterial gene expression 1 , 2 . The pioneering ribosome can both physically associate and kinetically coordinate with the RNA polymerase (RNAP) 3 - 11 , forming a signal-integration hub for co-transcriptional regulation that includes translation-based attenuation 12 , 13 and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 70 publications
13
120
2
1
Order By: Relevance
“…In wild-type E. coli , nusG and rho genes are essential; their deletions can be obtained only in specially engineered strains ( Leela et al, 2013 ) and confer significant growth defects. In contrast, neither gene is essential in B. subtilis ( Ingham et al, 1999 ), in which Rho has limited effects on gene regulation ( Nicolas et al, 2012 ), early stop codons do not induce polarity ( Johnson et al, 2020 ), and most transcription termination is induced by hairpin signals ( Mondal et al, 2016 ; Johnson et al, 2020 ). In contrast to E. coli , where NusG aids Rho in termination of rut -less RNAs ( Lawson and Berger, 2019 ), Rho-dependent termination in B. subtilis is strongly linked to cis -encoded C-rich RNA elements ( Johnson et al, 2020 ).…”
Section: Silencing Aberrant Transcriptionmentioning
confidence: 99%
“…In wild-type E. coli , nusG and rho genes are essential; their deletions can be obtained only in specially engineered strains ( Leela et al, 2013 ) and confer significant growth defects. In contrast, neither gene is essential in B. subtilis ( Ingham et al, 1999 ), in which Rho has limited effects on gene regulation ( Nicolas et al, 2012 ), early stop codons do not induce polarity ( Johnson et al, 2020 ), and most transcription termination is induced by hairpin signals ( Mondal et al, 2016 ; Johnson et al, 2020 ). In contrast to E. coli , where NusG aids Rho in termination of rut -less RNAs ( Lawson and Berger, 2019 ), Rho-dependent termination in B. subtilis is strongly linked to cis -encoded C-rich RNA elements ( Johnson et al, 2020 ).…”
Section: Silencing Aberrant Transcriptionmentioning
confidence: 99%
“…A recent report revealed that the B. subtilis and E. coli RNA polymerases transcribe RNA at significantly differing rates that may help to further explain differences in pausing requirements [71]. Structural switching of the pbuE riboswitch may be optimized for decoupling of transcription and the pioneering round of translation, whereas in E. coli a strong pause is required to promote aptamer folding in the presence of a potentially interfering ribosome.…”
Section: Plos Onementioning
confidence: 99%
“…Structural switching of the pbuE riboswitch may be optimized for decoupling of transcription and the pioneering round of translation, whereas in E. coli a strong pause is required to promote aptamer folding in the presence of a potentially interfering ribosome. Indeed, it is known that the E. coli ribosome can interfere with intrinsic terminator formation [72,73] whereas in B. subtilis this does not appear to be the case [71], further indicating that the co-transcriptional folding of the riboswitch may differ between the two organisms. Further, there are differences in the set of factors that influence transcription and its regulation between E. coli and B. subtilis; for example, B. subtilis lacks the Rho factor that is an important regulator of transcriptional termination in E. coli.…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, thereby synthesized enzymes could be produced close to each other and enable metabolic channeling (67). Finally, while Rho and transcription/translation coupling helps avoiding RNAP collisions and R-loops-with the downside of polarity-some bacterial types could have solved the traffic jam problem by evolving a different type of termination (19). In fact, interruption of non-translated transcripts may be detrimental for emergence of new catabolic operons: nosense mutations in lead genes could prevent expression of the whole cluster and curb evolution of downstream ORFs.…”
Section: Disruption Of Intracellular Crowding Enables Xyl Transcriptsmentioning
confidence: 99%
“…In other instances, a signal-recognition particle (SRP) is involved in the movement of mRNAs to the membrane, as translation of some mRNAs encoding innermembrane proteins produces a signal peptide that recruits such SRP and the complex leads the transcript to its intracellular address (15,16,18). Finally, Rho-dependent transcription termination in Bacillus subtilis is somewhat weak, and runaway, untranslated mRNAs are abundant (19). In sum, the fate of each transcript seems to be both gene (i.e.…”
Section: Introductionmentioning
confidence: 99%